KOMPETENSI PELAUT DALAM PENERAPAN INTERNATIONAL SAFETY MANAJEMEN CODE (ISM- CODE) - Andi Dachlan Sadly (RELASI : JURNAL EKONOMI, 2015)
Kelaiklautan is absolutely filled to the ship to sail, along with the development of the maritime world and the complexity of the problem, then IMO produces guidelanes on Management for Save Operation of ship and for pollution, effective implementation. or better known as the "International Safety Management Code" (ISM-Code), and consequently, all participants Member States should fully implement this rule. This study determine the competence of seafarers in applying the ISM - Code, corporate support, and the process of government oversight of the implementation of the rules that have been required of ships weighing more than the GT 500, using qualitative methods. The results showed that the competence of seafarers were largely meets the standards of Standards of Training Certification and Watchkeeping for Seafarers(STCW), but in the implementation of the ISM - Code there are obstacles in the form of execution that did not meet the standards set out in Safety Of Life At Sea(SOLAS) rules. Government oversight in this case kesyahbandaran seem indecisive. It is shown from the results of interviews and observations conducted by the researcher.